Improving the selection and development of influenza vaccine viruses – Report of a WHO informal consultation on improving influenza vaccine virus selection, Hong Kong SAR, China, 18–20 November 2015. Issue 8 (22nd February 2017) - Hampson, Alan; Barr, Ian; Cox, Nancy; Donis, Ruben O.; Siddhivinayak, Hirve; Jernigan, Daniel; Katz, Jacqueline; McCauley, John; Motta, Fernando; Odagiri, Takato; Tam, John S.; Waddell, Anthony; et al.
Abstract: Since 2010 the WHO has held a series of informal consultations to explore ways of improving the currently highly complex and time-pressured influenza vaccine virus selection and development process. In November 2015 experts from around the world met to review the current status of efforts in this field. Discussion topics included strengthening influenza surveillance activities to increase the availability of candidate vaccine viruses and improve the extent, timeliness and quality of surveillance data. Consideration was also given to the development and potential application of newer laboratory assays to better characterize candidate vaccine viruses, the potential importance of antibodies directed against influenza virus neuraminidase, and the role of vaccine effectiveness studies. Advances in next generation sequencing and whole genome sequencing of influenza viruses were also discussed, along with associated developments in synthetic genomics technologies, evolutionary analysis and predictive mathematical modelling. Discussions were also held on the late emergence of an antigenic variant influenza A(H3N2) virus in mid-2014 that could not be incorporated in time into the 2014–15 northern hemisphere vaccine. There was broad recognition that given the current highly constrained influenza vaccine development and production timeline it would remain impossible to incorporate any variant virus which emerged significantly long after the relevant WHO biannual influenza vaccine composition meetings. Discussions were also held on the development of pandemic and broadly protective vaccines, and on associated regulatory and manufacturing requirements and constraints. With increasing awareness of the health and economic burdens caused by seasonal influenza, the ever-present threat posed by zoonotic influenza viruses, and the significant impact of the 2014–15 northern hemisphere seasonal influenza vaccine mismatch, this consultation provided a very timely opportunity to share developments and exchange views. In all areas, a renewed and strengthened emphasis was placed on developing concrete and measurable actions and identifying the key stakeholders responsible for their implementation.